Development of Bangladesh with equity and justice : immediate tasks for the new government. (Centre for Policy Dialogue, 2009)
Papers presented at the Conference on Development with Equity and Justice: Immediate Tasks for the Newly Elected Government, held at Dhaka, Bangladesh in 2009; organised by Centre for Policy Dialogue, Bangladesh.